Avaliação dos parâmetros ecofisiológicos e de crescimento em rosa do deserto sob restrição hídrica associada ao filme de partícula de CaCO3 - Silveira, Maria Priscilla Celestino (2016)
Among the tropical ornamental plants, although the desert rose (Adenium obesum (Forssk.) Roem. e Schult.) is a little-known species, it presents a prosperous cultivation perspective. Aside from being an exuberant plant with several multi-colored flowers, this species also has as an advantage, a water and nutrients storage in its stem for dry periods or prolonged drought, working as an alternative for small and medium rural producers in semi-arid areas unequipped of an irrigation system. The association of this anatomic characteristic of the species to the use of the particle film may also be considered a strategy to minimize the effects of the hydro-deficit in high-temperature areas and low rainfall, improving the physiologic functions of the plants. Thus, in order to explore papers which analyze resistant species or techniques that enhance echo-physiologic functions, this study aims to evaluate the effects of hydro-restriction and the use of CaCO3 particle film in Adenium obesum associated to leaf gas exchange and growth parameters. The experiment was conducted in an ar-conditioned greenhouse, located at the Federal University (UFS) in São Cristóvão city, in the state of Sergipe. The seeds were obtained from a commercial supplier from São Paulo, and they were planted in trays and subsequently, the seedlings were transferred to 3-liter vases. After the transference and the plants acclimatization period, the samples were subjected to the effect or not, of the hidro-restriction and the use of CaCO3 particle film at a 5% concentration, as well as its absence. The leaf evolution parameters, as well as the echo-physiological and biometric ones were evaluated to the infliction of photosynthesis registered around 0 μmol CO2 m-² s-¹, to the samples subjected to hydro-restriction, those being subsequently hydrated and evaluated regarding their recovery of characteristics in comparison to those with no restriction. The following variables were evaluated: the plant height, number of leaves, stem diameter, length of central nerve (CNC); chlorophyll content (Chl a, Chl b, Chl total); leaf dry matter, stem and root and root volume, a chlorophyll fluorescence (F0, Fm, Fv/Fm), liquid photosynthesis rate (A), stomatal conductance (gs), transpiration (E), vapor pressure deficit (DPVfolha-ar), internal carbon concentration (Ci). The experiment in DIC was carried out in factorial function (plants with or without hydro-restriction and the use or not of the particle film analyzed over time) in nine repetitions, considering one plant per repetition. The hydro-restriction as a variable was shown to interfere in all analyzed variables negatively, except from Ci, in which higher means were verified. Due to the anatomic and physiologic characteristics of A. obesum, it has proved to be resistant to hydro-restriction treatment, and it also showed fast recovery of the echo-physiologic parameters and growth indicators after 38 days of irrigation interruption. The use of the film didn’t interfere with the characteristics of the species, and only showed significant effect to the Ci variable, presenting higher means in addition to the hydro deficit factor.